Numerical Analysis of Johnson-Cook Damage Model Parameters Effects on the Cutting Simulation of AISI 1045 - Sun, Yong; Li, Guohe; He, Zhen; Kong, Xiangcheng (Recent Patents on Engineering, 2022)
Background: The failure model is an important basis for research on material failure and fracture, and plays an important role in the finite element simulation of metal cutting. Johnson- Cook damage model is widely used to predict the onset of damage to many materials. Its damage evolution is controlled by five parameters. Objective: This study aimed to decrease the cost of damage parameters’ identification and find out the damage parameters which have a great influence on the simulation results. This work can provide assistance in the optimization and selection of constitutive model parameters. Methods: Suitable Johnson-Cook damage model parameters, which can be used in the metal cutting simulation of AISI 1045 steel, are selected by comparing the simulation results and the experimental results. The cutting process of AISI 1045 steel is simulated by changing the Johnson- Cook damage parameters in the ABAQUS/Explicit. Results: The relevance of cutting force, feed force, cutting temperature, and deformation coefficient with five Johnson-Cook damage parameters are determined. Conclusion: The finite element simulation results show that the Johnson-Cook damage model parameters D2 and D3 have the biggest impact on the cutting simulation of AISI 1045 steel. Meanwhile, different Johnson-Cook damage parameters would cause diverse changes in the simulation results.
Keywords: AISI 1045